Screening and management of sleep disorders in patients with fibromyalgia syndrome: a French multicentred, prospective, observational study protocol (FIBOBS). Issue 9 (30th September 2022) - Andre, Gilbert; Petitjean, Pauline; Haas, Victoria; Geraud, Eva; Fantini, Maria Livia; Creac'h, Christelle; Perez, Christèle; Bonnefoi, Marlène; Gadea, Emilie
Abstract : Introduction: Sleep disorders are still often underestimated in patient care management even though they are present in the criteria of the American College of Rheumatology for the diagnosis of fibromyalgia syndrome (FMS). The objective of this study will be to assess the current situation of sleep disorders in patients with FMS in France and to estimate its prevalence. Methods and analysis: The FIBOBS study is a multicentred, prospective, observational trial performed by 46 specialised chronic pain structures in France. Patients with FMS visiting for a first consultation or follow-up (if they have already been followed up for less than a year with a pain management service) will be included after giving their informed consent. Data will be collected through the physician questionnaire filled during the inclusion visit. Patient self-questionnaires will be completed from home. The primary outcome of the study will be to estimate the prevalence of sleep disorders classified into three categories: (a) poor sleep quality in general, (b) sleep apnoea syndrome and (c) restless legs syndrome, using self-administered questionnaires. Ethics and dissemination: This protocol is approved by the ethics committee Comité de Protection des Personnes ' Ile de France II' in accordance with French regulations. The results will be disseminated through peer-reviewed journals and conferences. Trial registration number: NCT04775368 .